Interleukin-36γ is causative for liver damage upon infection with Rift Valley fever virus in type I interferon receptor-deficient mice - Anzaghe, Martina; Niles, Marc A.; Korotkova, Eugenia; Dominguez, Monica; Kronhart, Stefanie; Ortega Iannazzo, Samira; Bechmann, Ingo; Bachmann, Malte; Mühl, Heiko; Kochs, Georg; Waibler, Zoe (Frontiers in Immunology, 2023)
Type I interferons (IFN) are pro-inflammatory cytokines which can also exert antiinflammatory effects via the regulation of interleukin (IL)-1 family members. Several studies showed that interferon receptor (IFNAR)-deficient mice develop severe liver damage upon treatment with artificial agonists such as acetaminophen or polyinosinic:polycytidylic acid. In order to investigate if these mechanisms also play a role in an acute viral infection, experiments with the Bunyaviridae family member Rift Valley fever virus (RVFV) were performed.Upon RVFV clone (cl)13 infection, IFNAR-deficient mice develop a severe liver injury as indicated by high activity of serum alanine aminotransferase (ALT) and histological analyses.Infected IFNAR -/-mice expressed high amounts of IL-36γ within the liver, which was not observed in infected wildtype (WT) animals. In line with this, treatment of WT mice with recombinant IL-36γ induced ALT activity. Furthermore, administration of an IL-36 receptor antagonist prior to infection prevented the formation of liver injury in IFNAR -/-mice, indicating that IL-36γ is causative for the observed liver damage. Mice deficient for adaptor molecules of certain pattern recognition receptors indicated that IL-36γ induction was dependent on mitochondrial antiviral-signaling protein and the retinoic acid-inducible gene-I-like receptor.Consequently, cell type-specific IFNAR knockouts revealed that type I IFN signaling in myeloid cells is critical in order to prevent IL-36γ expression and liver injury upon viral infection.Our data demonstrate an anti-inflammatory role of type I IFN in a model for virus-induced hepatitis by preventing the expression of the novel IL-1 family member IL-36γ.